2008
DOI: 10.1530/eje-08-0064
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in endocrine and fluid balance markers during high-intensity, steady-state, and prolonged endurance running: unexpected increases in oxytocin and brain natriuretic peptide during exercise

Abstract: Maintenance of fluid homeostasis during periods of heightened physical stress can be best evaluated in humans using exercise as a model. Although it is well established that arginine vasopressin (AVP), aldosterone and atrial natriuretic peptide (ANP) are the principle hormones regulating fluid balance at rest, the potential contributions of other related endocrine factors, such as oxytocin (OT) and brain natriuretic peptide (BNP), have not been well described during exercise. Seven endurance-trained runners co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 38 publications
6
85
1
Order By: Relevance
“…However, some effects were in the expected direction but statistical power was low, and we further cannot exclude the possibility that these variables did have independent effects on central OT. Cortisol, which could make cooperation condition-dependent [14] and can be suppressed by OT [28], was not associated with OT here, possibly because energy demand was not enough to elevate cortisol in this sample [16] (compared with extreme exercise [27]), or because salivary OT in men is not always associated with stress [21].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, some effects were in the expected direction but statistical power was low, and we further cannot exclude the possibility that these variables did have independent effects on central OT. Cortisol, which could make cooperation condition-dependent [14] and can be suppressed by OT [28], was not associated with OT here, possibly because energy demand was not enough to elevate cortisol in this sample [16] (compared with extreme exercise [27]), or because salivary OT in men is not always associated with stress [21].…”
Section: Discussionmentioning
confidence: 74%
“…Given that peripheral OT levels may track partner value [4], we speculate that this duration effect could facilitate familial social contact and help reinforce pair-bonding and parenting behaviour after male absence [1,2], which was probably common in our recent evolutionary history owing to the sexual division of labour [17]. Although correlated with distance travelled, the duration effect is unlikely owing to physical activity as neither duration nor OT change were associated with accelerometry counts or heart rates (table 1; although the correlation between OT change and heart rate was moderate but statistical power was low), and only extreme exercise may increase peripheral OT [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has also shown that [OT] P can activate the V2 receptor, causing APQ2 translocation and concomitant antidiuresis (19). However, unlike in animal studies, a regulatory role for OT in human osmoregulation remains equivocal (12,37).…”
Section: V2r Effects On Plasma Variablesmentioning
confidence: 99%
“…Oxytocin has been shown to increase directly after endurance running [22] and seems to have primarily parasympathetic actions such as slowing down the heart rate in trained individuals [23,24] a phenomenon related to training and overtraining syndrome [44]. This study aimed to investigate if analysis of Oxytocin levels could be an additional marker training stress such as overtraining syndrome since Oxytocin has been shown to have effects on stress management [1].…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin is also thought to work as an Anxiolytic as it decreases stress hormones in both humans and rats, and to modulate the physiological and behavioral responses to stress. Oxytocin also seems to have primarily parasympathetic actions and has been shown to increase directly after endurance running [22] and it facilitates the slowing down of the heart rate in trained individuals [23,24]. Physiological training stress can thus be used as a model to study the relationship between Oxytocin, mood and stress.…”
Section: Introductionmentioning
confidence: 99%